Membangun Kompetensi Profesionalisme Konselor Berwawasan Surah Al Ashr - Sari, Nina Permata; Setiawan, Muhammad Andri (Konselor, 2018)
There has been a lot of competence arranged professionalism counselor with the purpose to establish the existence of a counselor. However, it should be understood that the competence of counselor professionalism in its application is influenced by various things such as the personality of the counselor, the values and the belief norms held by the counselor in carrying out the counseling process. Each of the scopes has its own color in its application, however it must be admitted that the professional competence of the counselor in practice despite having a fixed standard but if each individual counselor applies is still unique. Especially for counselors with counseling approach of Islam the principle application of professional competence of counselor  based on source of Al Qur'an. In that case,  in the Qur'an surah Al 'Ashr although illustrated three verses but in fact when examined further is an insightful footing for Muslim counselors applying professionalism.There has been a lot of competence arranged professionalism counselor with the purpose to establish the existence of a counselor. However, it should be understood that the competence of counselor professionalism in its application is influenced by various things such as the personality of the counselor, the values and the belief norms held by the counselor in carrying out the counseling process. Each of the scopes has its own color in its application, however it must be admitted that the professional competence of the counselor in practice despite having a fixed standard but if each individual counselor applies is still unique. Especially for counselors with counseling approach of Islam the principle application of professional competence of counselor  based on source of Al Qur'an. In that case,  in the Qur'an surah Al 'Ashr although illustrated three verses but in fact when examined further is an insightful footing for Muslim counselors applying professionalism.